2013
DOI: 10.1186/2045-3329-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumors of the soft tissues: imaging features with histopathologic correlations

Abstract: PurposeTo describe the imaging features of soft tissue solitary fibrous tumors, with histopathological correlations and clinical outcome.Material and methodsTwenty-seven patients with histologically proven SFTs were retrospectively evaluated. Imaging studies included six radiographs, five U/S studies, eighteen CT scans, fourteen MRI exams, and one angiography.ResultsOn CT scans, two lesions were isodense and five were mildly hypodense compared to muscle while 11 lesions appeared heterogeneous-mixed of iso and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…[1] Positivity for CD34, bcl-2 and CD99 indicate SFT. [3,4] In our case, tumor showed positivity for CD34 and CD99. Behaviour of SFT is unpredictable.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…[1] Positivity for CD34, bcl-2 and CD99 indicate SFT. [3,4] In our case, tumor showed positivity for CD34 and CD99. Behaviour of SFT is unpredictable.…”
Section: Discussionsupporting
confidence: 48%
“…[1] It usually occurs in the pleura, but extra-pleural sites are also reported. [1][2][3][4] Occurrence at extra-pleural sites is rare and soft tissue sites account for 0.6% of all soft tissue tumors. [4,8] Extra-pleural sites include sub-cutaneous or deep soft tissue of extremity, head and neck, mediastinum, retroperitoneum, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Still, CT and MRI features of SFTs are nonspecific, revealing well-defined and often lobulated soft tissue space-occupying masses that displace adjacent anatomic structures. 18 , 19 For our 20 cases, 12/20 patients with SFTs who were diagnosed in our single hospital were located in extrapleural sites (60%). SFTs of different sizes had different features according to CT and MRI.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in 2005 Burstein et al reported that if two-thirds of patients with NCM have giant congenital melanocytic nevi, the remaining onethird have numerous lesions but no giant lesions (3). Generally NCM diagnosis is made in the first two years of life, but very rarely some adult cases are reported in the literature such as the patient described by Zhang et al in 2008 and others (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%